Standar Etika dan Tantangan Profesi Hukum Advokat di Era Digital - Ramadhan, Realizhar Adillah Kharisma (Indo-MathEdu Intellectuals Journal, 2024)
This study discusses the role of ethics in the legal profession in Indonesia, as well as the challenges faced by this profession in the digital era. Professional ethics for lawyers serve as the main foundation in maintaining integrity, credibility, and public trust in the legal system. Based on an analysis of the lawyer’s code of ethics, Law Number 18 of 2003, and related regulations, this study identifies the importance of implementing ethical principles such as integrity, honesty, and competence in legal practice. Violations of the code of ethics, as seen in the electronic ID card (e-KTP) corruption case, can damage public trust in both the legal profession and the legal system. This research uses a normative approach with doctrinal analysis of regulations and legal literature. The findings show that, although the lawyer's code of ethics provides guidelines to maintain professionalism, the digital era presents new challenges that require adjustments in ethical practices. In conclusion, to maintain the integrity of the legal profession and public trust in the legal system, lawyers must uphold ethical principles, adapt to technological developments, and ensure consistent application of the code of ethics